Interpersonal relations and work performance in tourist hotels of the department of Puno - Hancco Gomez, Miriam Serezade; Carpio Maraza, Amira; Laura Castillo, Zoraima Julieta (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2021)
Interpersonal relationships constitute a critical role in a company due to the interaction with people who hold different points of view, ideas, perceptions or training, which can affect job performance for good or bad, therefore, allowing or distracting the achievement of organizational objectives. In this context, the research aims: to analyze the interpersonal relationships of the employees of the hotels in the Puno department and to determine the work performance of the employees of the hotels in the Puno department. The methods frame a research with a quantitative approach, exploratory-descriptive scope and non-experimental design. The population is made up of 40 hotels categorized in three stars, from which a sample of 16 hotels has been obtained, which house 84 collaborators to be surveyed. The data collection technique was the survey and the instrument was the questionnaire for the interpersonal relationships variable, which contains 15 questions measured on a Likert scale and for the job performance variable, the evaluation was applied by the graphic scale method. The data processing has been done through the Excel spreadsheet and the SPSS statistical package. Through this, the frequencies and percentages of each variable and its dimensions were calculated. The results allow to conclude that the interpersonal relationships in the hotels of the Puno department according to the scale of the instrument used are good, thus the work performance of the employees of the hotels of the Puno department is good according to the graphic scale.